Thu gọn \(A=\frac{2x+|x-1|}{3x^2+2x-1}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a/4x\left(x-3\right)-3x\left(2+x\right)\\ =4x.x-4x.3-3x.2-3x.x\\ =4x^2-12x-6x-3x^2\\ =x^2-18x\\ b/2x\left(5x+2\right)+\left(2x-3\right)\left(3x-1\right)\\ =2x.5x+2x.2+2x.3x-2x.1-3.3x+3.1\\ =10x^2+4x+6x^2-2x-9x+3\\ =16x^2-7x+3\)
Ta có:
A = \(\frac{x^4-2x^2+1}{x^3-3x-2}\)
A = \(\frac{\left(x^2-1\right)^2}{x^3-4x+x-2}\)
A = \(\frac{\left[\left(x-1\right)\left(x+1\right)\right]^2}{x\left(x^2-4\right)+\left(x-2\right)}\)
A = \(\frac{\left(x-1\right)^2\left(x+1\right)^2}{x\left(x-2\right)\left(x+2\right)+\left(x-2\right)}\)
A = \(\frac{\left(x-1\right)^2\left(x+1\right)^2}{\left(x-2\right)\left(x^2+2x+1\right)}\)
A = \(\frac{\left(x-1\right)^2\left(x+1\right)^2}{\left(x-2\right)\left(x+1\right)^2}\)
A = \(\frac{\left(x-1\right)^2}{x-2}\)= \(\frac{x^2-2x+1}{x-2}\)
a: =18x^3y^2-12x^3y^3+6x^2y^2
b: (-3x+2)(5x^2-1/3x+4)
=-12x^3+x^2-12x+10x^2-2/3x+8
=-12x^3+11x^2-38/3x+8
c: =x^2-x-2+3x-x^2
=2x-2
d: =4x^2+12x+9-4x^2+25-(x-1)(x^2+12)
=12x+34-x^3-12x+x^2+12
=-x^3+x^2+46
a, \(4x\left(x-3\right)-3x\left(2+x\right)=4x^2-12x-6x^2-3x^2=-5x^2-12x\)
b, \(2x\left(5x+2\right)+\left(2x-3\right)\left(3x-1\right)=10x^2+4x+6x^2-11x+3\)
\(=16x^2-7x+3\)
c, \(\left(x-1\right)^2-\left(x+2\right)\left(x-2\right)=x^2-2x+1-x^2+4=-2x+5\)
d, \(\left(1+2x\right)+2\left(1+2x\right)\left(x-1\right)+\left(x-1\right)^2\)
\(=1+2x+2\left(x-1+2x^2-2x\right)+x^2-2x+1\)
\(=x^2+2+2\left(-x-1+2x^2\right)=x^2+2-2x-2+4x^2=5x^2-2x\)
a) \(\left(x-3\right)\left(x+7\right)-\left(2x-5\right)\left(x-1\right)\)
\(=\left(x^2-3x+7x-21\right)-\left(2x^2-5x-2x+5\right)\)
\(=\left(x^2+4x-21\right)-\left(2x^2-7x+5\right)\)
\(=x^2+4x-21-2x^2+7x-5\)
\(=-x^2+11x-26\)
b) \(-\left(3x+5\right)\left(2x-1\right)-\left[1-4\left(3x+2\right)\right]\)
\(=-\left(6x^2+10x-3x-5\right)-\left(1-12x-8\right)\)
\(=-\left(6x^2+7x-5\right)-\left(1-12x-8\right)\)
\(=-6x^2-4x+5-1+12x+8\)
\(=-6x^2+8x+12\)
F(\(x\)) = -2\(x\)4 + 3\(x^3\) - 4\(x\) + 2\(x^4\) - \(x^2\) - 3\(x^3\) - \(x\) + 1
F(\(x\)) = ( -2\(x^4\)+2\(x^4\)) + (3\(x^3\) - 3\(x^3\)) -(4\(x\) + \(x\)) + 1
F(\(x\)) = 0 + 0 - 5\(x\) + 1
F(\(x\)) = - 5\(x\) + 1
\(f\left(x\right)=-2x^4+3x^3-4x+2x^4-x^2-3x^3-x+1\)
\(f\left(x\right)=-2x^4+2x^4+3x^3-3x^3-4x-x-x^2+1\)
\(f\left(x\right)=-5x-x^2+1\)